2015
DOI: 10.1590/s1516-8913201400202
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Terminalia chebula Induces Apoptosis in Lung Cancer Cells Via a Mechanism Involving Mitochondria-mediated Pathways

Abstract: The current study was designed to evaluate the aqueous extract of Terminalia chebula activity, and the main pathway was detected on lung cancer by extracts of T. chebula. Aqueous extract of T. chebula was separated using a zeolite, and five fractions of T. chebula extract were obtained and analyzed by ultraviolet (UV) and infrared (IR) spectroscopy. Antiproliferative activity was evaluated by 3- (4,5-dimethylthiazol-2-yl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The reported IC 50 values against A-549 and MCF-7 were 208.16 ± 3.7, and 643.13 ± 4.2 µg/mL, respectively [15]. Furthermore, the aqueous extract of T. chebula was found to induce apoptosis in A-549 cell line via mitochondria-mediated pathway controlled by the Bcl-2 family members, Bcl-2, Bcl-xI and Bax proteins [16]. Similarly, in an in vivo study conducted by Ahuja et al (2013), it was concluded that the ethanolic extract of T. chebula significantly reduced the tumor growth in mice, with EAC induced cancer, apart from increasing their lifespan and restoring the haematological homeostasis [17].…”
Section: Introductionmentioning
confidence: 96%
“…The reported IC 50 values against A-549 and MCF-7 were 208.16 ± 3.7, and 643.13 ± 4.2 µg/mL, respectively [15]. Furthermore, the aqueous extract of T. chebula was found to induce apoptosis in A-549 cell line via mitochondria-mediated pathway controlled by the Bcl-2 family members, Bcl-2, Bcl-xI and Bax proteins [16]. Similarly, in an in vivo study conducted by Ahuja et al (2013), it was concluded that the ethanolic extract of T. chebula significantly reduced the tumor growth in mice, with EAC induced cancer, apart from increasing their lifespan and restoring the haematological homeostasis [17].…”
Section: Introductionmentioning
confidence: 96%
“…GA molecular mechanism showed a decrease in Ki-67 expression and promotion in cell apoptosis associated with the inhabitation of the Hippo pathway (Sun and Wang, 2020). T. chebula as a natural agent is a suitable candidate for further investigation in the treatment and cancer prevention (Wang et al, 2015).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…The final weight of the extracts was obtained, and the percentage yield of the extracts was determined. The extracts were stored in the dark at 4°C until further use (Wang et al, 2015). The percentage yield obtained was 23.36% (initial yield = 18.791 g and final yield = 4.390 g).…”
Section: Plant Materialsmentioning
confidence: 99%